Complete genome sequence of Ferroglobus placidus AEDII12DO. Issue 1 (July 2011) - Anderson, Iain; Risso, Carla; Holmes, Dawn; Lucas, Susan; Copeland, Alex; Lapidus, Alla; Cheng, Jan-Fang; Bruce, David; Goodwin, Lynne; Pitluck, Samuel; Saunders, Elizabeth; Brettin, Thomas; et al.
Abstract Ferroglobus placidus belongs to the orderArchaeoglobales within the archaeal phylumEuryarchaeota . Strain AEDII12DO is the type strain of the species and was isolated from a shallow marine hydrothermal system at Vulcano, Italy. It is a hyperthermophilic, anaerobic chemolithoautotroph, but it can also use a variety of aromatic compounds as electron donors. Here we describe the features of this organism together with the complete genome sequence and annotation. The 2, 196, 266 bp genome with its 2, 567 protein-coding and 55 RNA genes was sequenced as part of a DOE Joint Genome Institute Laboratory Sequencing Program (LSP) project.